Green skills in German manufacturing - Oliver Falck; Akash Kaura (CESifo GmbH, 2023)
Germany is a strong industrial nation with manufacturing contributing significantly to its economy. The country faces challenges including decarbonization, digitalization, and increased competition, especially in the automotive sector. Germany's automotive industry is vital to its economy, contributing around 9% of GDP and employing over 2.5 million people. The industry must adapt to these changes, requiring a skilled workforce with a focus on green technologies. The country has done a remarkable job in greening its manufacturing and green skills are quickly gaining prominence. After all, Germany is still a hotbed of innovation, but cannot afford to become complacent.
Keywords: 330